Plant Secondary Metabolism Engineering Methods and Applications - Fett-Neto, Arthur Germano (Methods in Molecular Biology, Methods and Protocols, 2010)
Plants have evolved an amazing array of metabolic pathways leading to molecules capable of responding promptly and effectively to stress situations imposed by biotic and abiotic factors, some of which supply the ever-growing needs of humankind for natural chemicals, such as pharmaceuticals, nutraceuticals, agrochemicals, food and chemical additives, biofuels, and biomass. In Plant Secondary Metabolism Engineering: Methods and Applications, expert researchers provide detailed practical information on some of the most important methods employed in the engineering of plant secondary metabolism pathways and in the acquisition of essential knowledge in performing this activity, including the significant advances and emerging strategies. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Plant Secondary Metabolism Engineering: Methods and Applications will aid scientists engaged in the challenging task of modifying some of the most intricate products of plant evolution and support their efforts directed toward the vital goal of sustainable natural chemicals